GASTROPODE DIVERSITY IN LAKE TONDANO AREA, NORTH SULAWESI, INDONESIA - Nonny Manampiring; Dany Posumah; Grichelle Tampi; Juninho Siwu; Vanessa Dagasina; Revolson Mege (Indonesian Biodiversity Journal, 2022)
The diversity of gastropod species is influenced by different substrates, environmental conditions, and human activities, so it is necessary to research the diversity of gastropod species in Lake Tondano. This study aims to obtain data on the diversity of gastropod species that live around Lake Tondano. The study was conducted in May 2022. The collection of research data on the diversity of gastropods in Lake Tondano begins by dividing the research area into five stations. Each station forms a Line transect of about 50 meters x 10 meters. At each line transect, 10 points will be determined in a zigzag manner for observation and sampling. The determination of the sample is carried out by purposive sampling. The gastropod samples will be identified and then documented, and the number will be recorded. Gastropods found around Lake Tondano are Achatinidae (Achatina fulica), Station 1: -, Station 2: -, Station 3: 1, Station 4: 1, Station 5: 1. Ampullariidae (Pila Ampullacea), Station 1 :173, Station 2 : -, Station 3: 73, Station 4: 117, Station 5: 57. Potamididae (Tylomeliana toradjarum), Station 1: 321, Station 2:2, Station 3: 123, Station 4: 3, Station 5 :-. Viviparidae (F. Javanica/ Filopaludina Javanica), Station 1: 85, Station 2: 161, Station 3: 335, Station 4: 315, Station 5: 153. Based on these data, the highest index is at point 3, and the density index is at point 1.